Pendampingan Masyarakat Peduli Ekowisata Mangrove di Kawasan Mangrove Tanjung Batu, Kecamatan Sekotong, Kabupaten Lombok Barat, Nusa Tenggara Barat: (Assistance for Mangrove Ecotourism Concerned Communities in the Tanjung Batu Mangrove Area, Sekotong District, West Lombok Regency, West Nusa Tenggara) - Markum; Umar Nasir; Misdarti; Alfian Pujian Hadi; Burhanuddin; Reni Retnowathi; M. Barmawi; Hanapi; Wahyu Wijayanti; Firman Ali Rahman; Dewi Putri Lestari (Prodi Tadris IPA Biologi UIN Mataram, 2024)
Assistance to people who care about mangrove ecotourism in mangrove areas is one of the monitoring and evaluation activities to maintain sustainability and increase the effectiveness of ecotourism programs in mangrove areas. The aim of community service activities in the Tanjung Batu mangrove ecotourism area, Sekotong District, West Lombok Regency is a follow-up to the urgency and relevance of the community assistance program caring for mangrove ecotourism in the mangrove area as a strategic step in maintaining the sustainability of the mangrove ecosystem which can improve the welfare of the local community. This service method is carried out through a process of mentoring and community empowerment through several stages, namely: field surveys, interviews, discussions, and formulating solutions for sustainable mangrove ecotourism. The results of service activities show that the Tanjung Batu mangrove ecotourism area, Sekotong District, West Lombok Regency is in good condition with facilities and infrastructure to support tourism activities. Improving the quality of management of mangrove ecotourism areas can be carried out through a strategy of regular monitoring and evaluation of environmental (water) quality conditions, management, organizational structure (pokdarwis), and evaluation of ecotourism management, and involving community participation in sustainable management of Tanjung Batu mangrove ecotourism.